Reduced prefrontal hemodynamic responses measured using near-infrared spectroscopy in adults with autism spectrum disorder - Kamikawa, Kohei; Yamamuro, Kazuhiko; Mizui, Ryo; Kashida, Natsuko; Ishida, Rio; Okada, Takashi; Iwata, Nakao; Makinodan, Manabu (Frontiers in Psychiatry, 2025)
AimFunctional neuroimaging studies have suggested that prefrontal cortex dysfunction occurs in individuals with autism spectrum disorder (ASD). Near-infrared spectroscopy (NIRS) is a noninvasive optical tool used to investigate oxygenation and hemodynamic responses in the cerebral cortex by measuring changes in oxygenated hemoglobin. Previous studies using NIRS have suggested that male children with ASD exhibit reduced hemodynamic responses in the dorsolateral prefrontal cortex; however, only a few studies examined this response in adults with ASD.MethodsWe examined the characteristics of prefrontal hemodynamic responses in 114 adults with ASD and 84 typically developing controls. Relative concentrations of oxygenated hemoglobin were measured with frontal probes every 0.1 s during the Stroop color-word task, using 24-channel NIRS.ResultsOur findings demonstrated that the oxygenated hemoglobin changes in the ASD group were significantly smaller than those in the control group at channels 19, 20, 23, and 24- located over the orbitofrontal cortex and frontal pole (p <0.05 for all three channels). The differences in oxygenated hemoglobin changes at Ch 20 were significantly correlated with the Autism-Spectrum Quotient Japanese version (AQ-J) total score and attention switching score, which is a symptom cluster of AQ-J (p = 0.043 and p = 0.009, respectively).ConclusionAdults with ASD have reduced prefrontal hemodynamic responses as measured using near-infrared spectroscopy and the reduced activity of the frontal pole in particular is related to reduced attentional function.